A Systematic Scoping Study of the Socio‐Economic Impact of Rift Valley Fever: Research Gaps and Needs. (24th September 2014) - Peyre, M.; Chevalier, V.; Abdo‐Salem, S.; Velthuis, A.; Antoine‐Moussiaux, N.; Thiry, E.; Roger, F.
Summary Rift Valley fever (RVF) is a severe mosquito‐borne disease affecting humans and domestic ruminants. RVF virus has been reported in most African countries, as well as in the Arabic Peninsula. This paper reviews the different types of socio‐economic impact induced by RVF disease and the attempts to evaluate them. Of the 52 papers selected for this review, 13 types of socio‐economic impact were identified according to the sector impacted, the level and temporal scale of the impact. RVF has a dramatic impact on producers and livestock industries, affecting public and animal health, food security and the livelihood of the pastoralist communities. RVF also has an impact on international trade and other agro‐industries. The risk of introducing RVF into disease‐free countries via the importation of an infected animal or mosquito is real, and the consequent restriction of access to export markets may induce dramatic economic consequences for national and local economies. Despite the important threat of RVF, few studies have been conducted to assess the socio‐economic impact of the disease. The 17 studies identified for quantitative analysis in this review relied only on partial cost analysis, with limited reference to mid‐ and long‐term impact, public health or risk mitigation measures. However, the estimated impacts were high (ranging from 5 to 470 million USD losses). To reduce the impact of RVF, early detection and rapid response should be implemented. Comprehensive disease impact studies are required to provide decision‐makers with science‐based information on the best intervention measure to implement ensuring efficient resource allocation. Through the analysis of RVF socio‐economic impact, this scoping study proposes insights into the mechanisms underpinning its often‐underestimated importance. This study highlights the need for comparative socio‐economic studies to help decision‐makers with their choices related to RVF disease management.